The Effectiveness of the Implementation of Risk Management at PT. XYZ Tbk - Atmadja, Jemmy; Tewu, Denny (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effectiveness of risk management implementation at PT XYZ Tbk in managing the company's liquidity and operational risks. The findings indicate that effective risk management significantly enhances the company's operational stability and financial performance, despite revenue fluctuations in certain periods. The implemented approach includes systematic identification, measurement, mitigation, and risk management. These strategies successfully helped the company achieve consistent net profit growth, even amidst challenges such as market changes and external risks. Through product diversification, quality control, and adaptive strategies, PT XYZ Tbk maintained its competitive edge in the market. This study highlights the importance of risk management as a tool not only for mitigating losses but also for creating opportunities for better growth.